Prevalence and risk factors of cardiovascular disease among people living with HIV in the Asia-Pacific region: a systematic review - Witchakorn Ruamtawee; Mathuros Tipayamongkholgul; Natnaree Aimyong; Weerawat Manosuthi (BMC, 2023)
Abstract Background Cardiovascular diseases (CVD) due to atherosclerosis have become one of the major causes of death among people living with HIV (PLHIV) since effective antiretroviral therapy (ART) has been available throughout the world. However, the epidemiologic evidence of this problem from the Asia-Pacific region remains unclear. We conducted a systematic review of the situation and risk factors for CVD among PLHIV in countries with the greatest impact of CVD attributable to HIV in the Asia-Pacific region. Methods A systematic search in PubMed/MEDLINE, EMBASE, and the Cochrane Database of Systematic Reviews databases for articles published before 2019 was conducted. Publications reported situations and risk factors both traditional and HIV-specific for CVD among PLHIV in the region were included. Two reviewers working on duplicate and quality assessments, independently extracted data, and thematically analyzed the data. Results Among PLHIV, the prevalence of subclinical CVD ranged from 10 to 28% and the incidence rate of clinical CVD ranged from 0.37 to 1.17 /100 person-years. Clinical CVD was frequently observed in the early era of the highly active antiretroviral therapy. A higher prevalence of subclinical CVD such as abnormal cIMT and carotid plaques was frequently observed in the PLHIV rather than in the nonHIV population and a high proportion of early onset of CVD was found among young PLHIV adults. The traditional risk factors for CVD such as hypertension, diabetes and smoking behavior were prevalent in both PLHIV and nonHIV populations ranging from 5 to 45%. HIV-specific risk factor, and lower CD4 presented almost twice the significantly increased risks for CVD while the synergistic interaction among traditional risk factors, i.e., diabetes mellitus, dyslipidemia and family history steeply increased the risk for CVD among PLHIV by almost 20 times. Conclusion The limited existing data suggested the risk of early CVD among PLHIV. We identified the crucial gaps in HIV/CVD work from the Asia-Pacific region and recommended longer prospective studies with larger sample sizes or meta-analyses to better capture CVD risk and interactions of crucial risk factors of this vulnerable population in this region. Registration number INPLASY202290108 ( https://inplasy.com/inplasy-2022-9-0108/ ).